UPAYA MENINGKATKAN PRESTASI BELAJAR MATEMATIKA DENGAN MENGGUNAKAN PBL BERBANTUAN MEDIA SEMPOA PADA OPERASI HITUNG SISWA MI - Setiyadi, Desi; Rohayati, Ika; Zubaidi (JISPE Journal of Islamic Primary Education, 2024)
The PBL model assisted by abacus media can improve students' mathematics learning achievement in arithmetic operations material because there are quite a few children whose learning achievement tends to be low in mathematics. This research aims to describe the increase in mathematics learning achievement using the PBL model. This research is Classroom Action Research which was carried out in two cycles with two meetings in each cycle. The subjects in this research were 25 students consisting of 10 male students and 15 female students at MI Nurul Falah. The data collection technique consists of three stages, namely observation, testing, and documentation. This research was carried out in 2 cycles, with each cycle consisting of: 1) Planning, 2) Implementation, 3) Observation, 4) Reflection. The data analysis technique is to see the increase in learning outcomes from 2 learning cycles with a limit of 80% reaching a KKM score of 60. The research results found that after implementing the learning method with the help of the abacus media, the test results in cycles I and II showed that students' learning achievement scores increased. 22 students or 88% of the total number of students have completed and 3 others have not yet finished. If compared with the learning achievement in cycle I, 60% of students had completed their studies, then the student achievement score increased by 28% in the number of students who had completed their studies. From the explanation above, it can be concluded that classroom action research carried out by researchers can improve student learning achievement in the field of mathematics.